The “arrhythmic” presentation of peripartum cardiomyopathy: case series and critical review of the literature - Peretto, Giovanni; Micaglio, Emanuele; Ciconte, Giuseppe; Maia, Marianna; Luzzi, Martina; Cariello, Marianna; Bonfanti, Adele Gabriella Rosa; Lazzeroni, Davide; Anastasia, Luigi; Cavoretto, Paolo; Chieffo, Alaide; Della Bella, Paolo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Peripartum Cardiomyopathy (PPCM) is a polymorphic myocardial disease occurring late during pregnancy or early after delivery. While reduced systolic function and heart failure (HF) symptoms have been widely characterized, there is still lack of reports about the arrhythmic manifestations of the disease. Most importantly, a broad range of unidentified preexisting conditions that may be missed by general practitioners and gynaecologists, are to be considered in differential diagnosis. The issue is relevant, since some arrhythmias are associated to sudden cardiac death occurring in the young, and the overall risk does not cease with the early postpartum timeframe. The aim of the present manuscript is: 1) to report a case series of 16 patients diagnosed with PPCM following arrhythmic clinical presentation, and: 2) to present an updated review of the literature about the arrhythmic manifestations of PPCM. In particular, the clinical usefulness of an extensive multimodality diagnostic workup, as well as a multidisciplinary management fostering personalized medicine, are hereby described.